(untitled) (Acta Scientiarum. Biological Sciences, 2016)
The objective was to create, validate and apply a measurement scale on environmental practices for teachers of various educational areas (exact sciences, humanities, natural sciences and Portuguese), from six public high schools in the city of Patos, Paraíba. To that end, it was created a questionnaire related to the topic, consisting of 24 items in the Likert scale model, being statistically validated as its consistency and reliability by factor analysis and by the Î±-Cronbach’s test. The assessed measurement scale has been validated (n = 34) with the exclusion of five items, getting excellent Î±-Cronbach’s coefficient (0.95). In the application of the questionnaire (n = 68), most teachers had social and environmental practices little consistent with environmentally sustainable practices. The results suggest that the high school teachers of the surveyed public schools have inadequate knowledge and/or practices for teaching Environmental Education, revealing that, probably, the students are not receiving basic environmental knowledge for their critical and reflective thinking on the various environmental problems.